Integrating ERC-20 tokens into a blockchain-based charity system a decentralized approach to transparent donations - Bennaoui, Imad Eddine; Lalmi, Mohamed Abderahmane; Chaïb, Noureddine (Laghouat : Université Amar Telidji - Département d'informatique, 2025)
Traditional charity donation systems often suffer from a lack of transparency, high transaction fees, and donor distrust. Many`donors are unable to verify how their funds are utilized, leading to concerns about fraud, inefficiency, and mismanagement. To address these challenges, this research explores the integration of ERC-20 tokens into a blockchain-based charity system, leveraging smart contracts`to ensure secure, transparent, and auditable transactions. The proposed system utilizes Ethereum-based smart contracts to automate donation processing, elim- inating the need for intermediaries and`reducing transaction costs. By implementing a decentralized application (dApp, a blockchain-powered application) with Web3 (a set of JavaScript libraries enabling interaction with the Ethereum blockchain), donors can track their contributions in real-time, ensuring that funds are only accessible to verified charities. The platform is developed using`Solidity for`smart contracts, Hardhat for blockchain testing, and React.js with Ethers.js for`the user interface. To evaluate the system’s efficiency, we analyze gas fees, transaction speed, security risks,`and user`adoption challenges. Experimental results demonstrate that blockchain-based donations can`significantly improve trust, transparency, and operational efficiency compared to traditional systems.`However,`chal- lenges such as scalability, regulatory concerns, and`smart contract vulnerabilities remain`areas`for further`improvement. This research contributes to the growing field`of decentralized`philanthropy, showcasing`how`blockchain`and ERC-20 tokens can`revolutionize the`way`charitable`donations are`managed.`Future`work`may explore Layer 2 scaling solutions to reduce fees and DAO (Decentralized`Autonomous`Organization)- based governance to enhance community-driven charity initiatives.